Pengaruh Pertumbuhan Dana Pihak Ketiga Terhadap Laba Perbankan Syariah di Indonesia - Nirwana, Lutfiyah Putri; Septiarini, Dina Fitrisia (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research was aimed to find out the partial asnd simultaneous effect of wadiah current account, wadiah savings, mudharabah saving, and mudharabah deposits to profits in Islamic Banking. This research used quantitative approach. Statistical tool used is the multiple regression time series. The population in this research was Islamic banking industry recorded in Indonesian bank. The sample used is the Islamic Banks and Islamic Business Unit which data summarized in statistical reports of Islamic banking. The research period is January 2009 - October 2014. The simultaneous test resulst were wadiah current account, wadiah savings, mudharabah saving, and mudharabah deposits simultaneously had significant effect on profits of Islamic banking. The partial test showed that wadiah savings has significant effect against Islamic banking profit whereas of wadiah current account, mudharabah saving, and mudharabah deposits has no significant effect to Islamic banking profit.